The dogit ordered generalized extreme value model - Fry, T.R.L.; Harris, Mark (BLACKWELL PUBLISHING, 2005)
This paper introduces the Dogit ordered generalized extreme value (DOGEV) model, for handling discrete variables that are ordered and heterogeneous. In particular, the DOGEV model can be applied to questionnaire responses on questions allowing a discrete set of ordered possible responses, where there is a preference for particular responses and possibly multiple modes in the data. The DOGEV model combines a model for choice set generation with the ordered generalized extreme value model. The paper illustrates the model using two empirical examples: a model of inflationary expectations and a model for students' evaluations of teaching. © 2005 Australian Statistical Publishing Association Inc.